Utilization of sago starch (Metroxylon sagu.Rott)in snack food preparation - Baylon, Janice Nones (2002.)
Sago starch was uilized in the preparation of shrimp-paste (okoy), rice pudding (cuchinta) and cookies.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Sago starch; Snack food